2016
DOI: 10.1080/09712119.2016.1206904
|View full text |Cite
|
Sign up to set email alerts
|

Effect of crumbled diet on growth performance, market day age and meat quality of growing-finishing pigs

Abstract: This study was conducted to determine the effect of crumbled diet on growth performance, market day age, and meat quality of growing-finishing pigs. A total of 120 crossbred pigs [(Landrace × Yorkshire) × Duroc] with an average initial body weight (BW) of 25.89 ± 1.93 kg at 68 days of age were randomly allotted to 2 experimental diets based on initial BW (15 replicate pens per treatment, 4 pigs per pen; 2 barrows and 2 gilts). The trial lasted for 120 days. Dietary treatments included: (1) T1 (mash diet); (2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
3
0
3
Order By: Relevance
“…La CRA y el color son atributos importantes que determinan el atractivo visual y la terneza de la carne (32,33) . Los valores observados en este experimento, fueron similares entre tratamientos, y concuerdan con los reportados previamente (34,35) en cerdos de finalización. En el presente trabajo, la carne de cerdos que recibieron alimento húmedo tuvo valores de dureza menores a la de cerdos que recibieron alimento seco, lo cual es indicativo de mayor terneza (36) , que es una de las características más importantes de la calidad de la carne (32,37) .…”
Section: Discussionunclassified
See 1 more Smart Citation
“…La CRA y el color son atributos importantes que determinan el atractivo visual y la terneza de la carne (32,33) . Los valores observados en este experimento, fueron similares entre tratamientos, y concuerdan con los reportados previamente (34,35) en cerdos de finalización. En el presente trabajo, la carne de cerdos que recibieron alimento húmedo tuvo valores de dureza menores a la de cerdos que recibieron alimento seco, lo cual es indicativo de mayor terneza (36) , que es una de las características más importantes de la calidad de la carne (32,37) .…”
Section: Discussionunclassified
“…En el presente estudio, no se encontraron diferencias entre tratamientos en las variables cromáticas L*, a*, b*, C y H, que determinan el color. Comparado con resultados de investigaciones previas (34) , los valores de luminosidad (L*) en el presente trabajo para la carne de cerdos alimentados con AH y AS (53.6 y 54.0, respectivamente; Cuadro 4) fueron indicativos de carne "normal" (39) . Valores de L* de 58 son indicativos de carne PSE (pálido, suave, exudativo), mientras que valores inferiores a 52 indican la condición de ASD (oscuro, firme, seco) (39,40,41) .…”
Section: Discussionunclassified
“…Choi et al (1986) reported that chickens fed the crumbled starter diet had greater intake and Reece et al (1984) observed that pigs fed a high-energy crumble and high-protein profile had the best feed conversion efficiency. Also, Nguyen et al (2017) reported a greater ADG and feed efficiency (FE) in pigs fed a crumble diet rather than mash diet for identical feed intake. However, no research has investigated the effect of crumbled corn on BW gain and metabolic response in dairy heifers.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies on animal diets seek strategies to improve feed efficiency, which are of particular interest to increase productive efficacy and reduce environmental impacts ( Aarnink & Verstegen, 2007 ; Clark & Tilman, 2017 ). In this sense, exogenous enzymes improve feed efficiency and reduce feeding costs in the animal production industry ( Adeola & Cowieson, 2011 ; Upadhaya, Park, Lee & Kim, 2016a ), as pig feed accounts for 55–75% of total production costs ( Nguyen, 2017 ).…”
Section: Introductionmentioning
confidence: 99%